The functional ecology of Eastern Rûens Shale Renosterveld - Cowan, Oliver (Department of Environmental and Geographical Science, 2020)
Globally, ecosystems are under mounting pressure as biodiversity is lost at an ever increasing rate due to drivers such as habitat destruction and climate change. The systematic degradation of natural habitats witnessed today is often accompanied by a loss of ecosystem functioning and services which not only endangers the future of humankind but has consequences for all life on earth. To manage the ecological challenges facing us there is an urgent need to increase our understanding of how ecosystems function, the relation/ship between biodiversity and ecosystem functioning, and the effect habitat degradation can have on this relationship. Eastern Rûens Shale Renosterveld, located in the Overberg region of South Africa, is a vegetation type both critically endangered and poorly understood. Centuries of agricultural activity in the region has resulted in a landscape typified by fragments of pristine vegetation, in addition to communities in various states of degradation, embedded in an agricultural matrix. The current quantities of pristine vegetation are inadequate to meet conservation goals and conservation efforts are further challenged by the fact that little is known of the functional ecology of not only pristine fragments of Renosterveld, but the degraded communities in various stages of secondary succession. The overarching aim of this thesis is to better understand the relationship between biodiversity and ecosystem functioning across a degradation gradient in critically endangered Renosterveld vegetation within an agricultural landscape in South Africa. To achieve this, a variety of methods were employed using different lenses of analysis. In Chapter 2, I studied the components of biodiversity to assess the relationship between taxonomic and functional diversity indices and investigate the effect of habitat degradation. In Chapters 3 and 4, I used litter traps to investigate the effect of plant litter type, season and habitat degradation on litter decomposition rates and Springtail (Collembola) community dynamics, respectively. Finally, in Chapter 5, I constructed three high-resolution plant-pollinator networks from sites with distinct land-use histories and with different above-ground vegetation communities. The results revealed a complex association between different taxonomic and functional diversity indices, influenced by habitat degradation, with potential ecological and conservation implications. Particularly, the loss of functional redundancy in degraded sites is likely to reduce resilience to future environmental perturbations which may reduce ecosystem functions. Conversely, the similarities in both taxonomic and functional diversity indices between pristine and moderately degraded sites may be cautiously interpreted as the occurrence of successful passive restoration. Litter decomposition rates were shown to be variable with litter type and season revealed as important controlling factors. Although degradation did not appear to significantly affect iv decomposition rates, the initial nutrient content of litter appears to correlate with decomposition rate and it can be expected this ecosystem function will be accelerated where habitat degradation results in shifts in above-ground vegetation and subsequent litter input, specifically where the cover of non-native, nitrogen-rich annual species is increased. There was found to be a significant impact of litter type on community composition, and of sampling day on species richness, abundance and community composition, in Springtail communities. Despite the overall lack of effect of degradation on Springtail community dynamics, the abundance of the non-native Entomobrya multifasciata in degraded sites, and its absence from pristine sites, raises the intriguing possibility of its suitability as a bioindicator for habitat degradation. Comparisons to similar global studies revealed the Renosterveld networks to be highly functionally specialized. Assessing network dynamics across a degradation gradient showed the impact of above-ground vegetation structure on network properties with the more open and diverse vegetation structure and floral resources provided by the highly degraded site resulting in network indices more similar to that of the pristine site when compared to the relatively structurally uniform moderately degraded site. Although this thesis has enhanced our understanding of the functional ecology of Renosterveld, it has also highlighted knowledge gaps which still exist. Creating and collating a database of functional trait data can provide the building blocks for future ecological work. Furthermore, to truly gain a mechanistic understanding of the biodiversity-ecosystem function relationship one needs to utilise an integrated analysis which considers different facets of biodiversity, particularly functional diversity, across multiple trophic levels while simultaneously acknowledging the legacy effects that distinct land-use histories can impose at the community level.